4q12–4q21.21 deletion genotype–phenotype correlation and the absence of piebaldism in presence of KIT haploinsufficiency. (29th October 2014) - Hemati, Parisa; du Souich, Christèle; Boerkoel, Cornelius F.
<x xml:space="preserve">Abstract</x> Chromosome 4q deletion syndrome is a rare intellectual disability disorder caused by a variety of non‐recurrent deletions of 4q. We describe the evolution of the phenotypic features of a female patient with a previously unreported deletion of 4q12–4q21.21 (hg 18; 54, 711, 575–79, 601, 919). By review reported individuals with interstitial deletions extending telomeric from 4q12 have syndromic intellectual disability with variable piebaldism. We expand the phenotype to include dolichocephaly, pectus excavatum, hip dysplasia, pes planus, myopia, lens opacities, and an absence of spoken language but not of communication through sign. The proposita also did not have piebaldism suggesting again that piebaldism arises from a mechanism more complex than simple haploinsufficiency of KIT. Comparing deletions among affected individuals localizes the critical interval within 4q12–4q13.1, although the absence of molecular boundaries for nearly all reported cases precludes precise delineation and genotype–phenotype correlation. © 2014 Wiley Periodicals, Inc.